Knowledge and awareness of AIDS among first year students of MBBS, BDS and BPT of Sumandeep Vidyapeeth University, Piparia- Vadodara - Chauhan, Grishma; Chhaya, Jatin; Karve, Sanidhya; Kankrecha, Ronak; Khurana, Dhruval (International Journal Of Community Medicine And Public Health, 2018)
Background: Catastrophic potential of the pandemic of AIDS may still not have been fully apprehended in 21st century, even though disease was exploded since 1981. Lack of public health awareness is only identifiable factor that is responsible for disastrous effect of HIV/AIDS. It is more even danger if future doctors unaware of diseases dynamics of HIV infection or AIDS diseases. So, the current study was planned to know level of awareness regarding of HIV/AIDS among medical and paramedical students of Sumandeep Vidhyapeeth University. Methods: Two hundred and eighty five students of Sumandeep Vidhyapeeth University were interviewed with the help of pre-designed questionnaire to know the awareness of HIV/AIDS among students. Results: The students were knowledgeable about causative agent and modality of diagnosis. However, only half of students were agreed with the fact that, the treatment is available for AIDS. On contrary, 24.60% students had wrong belief that the vaccine against HIV/AIDS is available. A very few number of students had the misconceptions about modes of transmission. Knowledge of prevention of HIV infection was good among students. Media and doctor/ health worker were the most frequently reported sources of information as reported by 56.49%% and 34.39% of the students respectively. Conclusions: The students had a satisfactory knowledge on many aspects of HIV/AIDS, but also along with some misconception about transmission of disease.